Meta-Analysis the Effect of Complementary Feeding Practice on Stunting in Children Aged 6-59 Months - Babys, Isna Yuswella; Dewi, Yulia Lanti Retno; Rahardjo, Setyo Sri (Journal of Maternal and Child Health, 2022)
Background: A child's ability to achieve growth standards is determined by the adequacy of food intake. Malnutrition in toddlers increases the risk of stunting, which is a serious problem. Stunting is closely related to neurocognitive development, risk of non-communicable diseases, and decreased productivity. Appropriate complementary feeding is an important milestone in efforts to improve survival and promote healthier child growth and development and can significantly reduce stunting. This study aims to estimate the magnitude of the effect of poor complementary feeding practices on the incidence of stunting in toddlers using a meta-analysis study. Subjects and Method: The meta-analysis was carried out with the initial step of formulating the research problem using the PICO technique. The study population were children aged 6-59 months with poor complementary feeding, compare with good complementary feeding. The study outcome was stunting. Articles were selected from Google Scholar, PubMed, Springer Link, and Research Gate databases. The keywords used were "complementary Feeding practice" OR "meal frequency" OR "dietary diversity" AND "Stunting". The inclusion criteria were full text, observational studies, and the results reported in Adjusted Odds Ratio (aOR). Analysis of articles using RevMan 5.3. Results: A meta-analysis involved 16 articles. The results showed that the low variety of complementary feeding increased the incidence of stunting 1.72 times compared to various types of complementary feeding (Aor= 1.72; 95% CI= 1.54 to 1.92; p < 0.001). Infrequent complementary feeding increased the incidence of stunting by 1.85 (aOR= 1.85; 95% CI 1.34 to 2.55; p <0.001). Conclusion: The diversity of types of complementary foods and low frequency of giving complementary foods increase the incidence of stunting in children aged 6-59 months. Keywords: complementary feeding practice, feeding frequency, food diversity, stunting. Correspondence: Isna Yuswella Babys. Master’s Program in Public Health Sciences, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: isnababys@gmail.com. Mobile: 082354707563.